PROBLEMATIKA PASCA PEMEKARAN DI DESA BANTAN TUA BERDASARKAN PERATURAN DAERAH KABUPATEN BENGKALIS NOMOR 09 TAHUN 2012 TENTANG PEMBENTUKAN DESA BARU DI KECAMATAN BANTAN KABUPATEN BENGKALIS - Alfan, Agus; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
His paper aims to determine the factors that contribute to the expansion in the village of Bantan Tua in 2012 and the problems that occur after the division in the village of Bantan Tua based Bengkalis District Regulation No. 09 Year 2012. In addition, are the focus of this study is problematic post-expansion occurs in the village of Bantan Tua Regional Regulation Number Kabupuaten Bengkalis 09 In 2012, causing symptoms and problems that occur after the realization of the expansion in 2014 until today. The method used in this research is using descriptive qualitative method. Data collection techniques using field studies and literature with primary and secondary data sources is to conduct direct observation of the object under study, and interviews where the researcher held a question and answer directly to the informant in connection with the problems examined and supported by secondary data.The results showed that the division in the village of Bantan Tua had no significant impact that can be seen from the factors that contribute to the expansion in the village of Bantan Tua in 2012 that the motive for efektifvitas efficiency of public services and government administration village; tendency to homogeneity between ethnic Malay and Javanese; their physical indulgence which is guaranteed by the Act, and the problems that occur after the division in the village of Bantan Tua based Bengkalis District Regulation No. 09 In 2012, namely violence between youths and the village of Bantan Tua and Pasiran; annexation and capital problems Bantan Tua Village; the seizure of assets.Keywords: Problematic, Expansion, Bantan Tua Village